Salt, glucose, glycine, and sucrose protect Escherichia coli O157:H7 against acid treatment in laboratory media. (December 2021) - Bae, Young-Min; Song, Hana; Lee, Sun-Young
Abstract: This study investigated the effects of combinations of acetic or malic acid and various solutes (salt, glucose, glycine, or sucrose) on the survival of Escherichia coli O157:H7 in laboratory broth. Additionally, the effectiveness of combining organic acids and various concentrations of salt (0–18%) or sucrose (0–100%) with different water activity values against E. coli O157:H7 were evaluated. For treatment of 1% malic acid, the addition of 3% salt showed synergistic effect. Whereas, when 3% salt, glucose, glycine, or sucrose was added to 1% acetic acid, the solutes antagonized the action of the acid against E. coli O157:H7. Acetic, lactic, or propionic acid combined with salt at either 7 or 9% or sucrose at 60, 80, or 100% resulted in the highest resistance of E. coli O157:H7. From a result of evaluating the membrane fatty acid (MFA) composition of cells, salt or sucrose significantly increased levels of saturated fatty acids (SFAs) or SFAs and cyclopropane fatty acids, respectively. From the results of this study, the addition of solutes and organic compounds may increase the tolerance of E. coli O157:H7 to acetic, lactic, and propionic acid treatments and that the salt or sucrose significantly affects cell MFA composition. Highlights: Salt, glucose, glycine, and sucrose protect E. coli O157:H7 against acid treatment. In combination, 1% malic acid and 3% salt synergistically inhibit E. coli O157:H7. Salt or sucrose treatment increases fatty acids in the E. coli O157:H7 membrane.